PENGEMBANGAN KURIKULUM PAI : ANALISIS KOMPONEN - KOMPONEN KURIKULUM DALAM PEMBELAJARAN ANTARA TUJUAN MATERI, METODE, DAN EVALUASI - Vihas Ariski Sunadi (ADISAM PUBLISHER, 2026)
Curriculum development in Islamic Religious Education plays a central role in shaping students’ intellectual and spiritual character. This paper discusses the integration of curriculum components including objectives, content, methods, and evaluation in the learning process. The discussion is based on conceptual analysis drawn from authoritative books written by Indonesian scholars in Islamic education and educational evaluation. The findings indicate that learning objectives function as the primary foundation that determines the direction of content selection, instructional strategies, and assessment design. Relevant and systematic content must be aligned with appropriate teaching methods to ensure meaningful internalization of Islamic values. Comprehensive evaluation covering cognitive, affective, and psychomotor aspects ensures that learning outcomes reflect both understanding and practice. The integration of these components creates a coherent and effective Islamic Religious Education curriculum.